The Fruit of Her Labor : Promoting Gender-Equitable Agribusiness in Papua New Guinea - World Bank; International Finance Corporation (Washington, DC, 2015)
The overall goal of this report is to assist the World Bank Group (WBG) to achieve greater impact for women from its current activities in agribusiness in Papua New Guinea (PNG), and to provide clear recommendations on additional interventions aimed at improving outcomes for women. The report focuses on the supply chains for coffee, cocoa, and horticultural products (fresh produce), as there is a wealth of knowledge on these supply chains and on gender issues, and these provide the best opportunity to identify entry points for follow-up activities. Given the importance of smallholders in PNG, and the need to understand gender dynamics in farming, this report pays particular attention to the roles and constraints faced by smallholders, without in so doing wishing to diminish the importance of the roles played by other actors in these supply chains.